(untitled) (Veterinary Science, 2019)
In horses production and health, nutrition is critical; equines are non-ruminant herbivores and knowing the quality of forages that graze, is essential for nutritional assessment. Thus, we set out to evaluate the proportion of particle sizes of fresh feces of horses that graze different types of forages. We used the commercial instrument Nasco Digestion Analyzer to wash the samples of fresh feces and pass them through a structure of 3 stainless steel sieves with decreasing pore diameter, being: A:> 4.8 mm; B: 4.8-3.2 mm; C: 3.2-1.6 mm and D: <1.6 mm, the remnant that escapes. 31 samples of fresh feces were obtained from adult Race Purebred Horse mares. The treatments were: 1. Diet Pp (n: 9) consociated pasture; 2. Diet Ss (n: 8) soy summer greengrass; 3. Diet Mn (n: 7) corn summer greengrass and 4.Diet Aa (n: 7) oatmeal summer greengrass. The forage samples were analyzed for dry matter (MSF), in vitro digestibility (DIG), fiber in neutral detergent (NDF) and fiber in acid detergent (ADF). Our results show that the proportions accumulated by particle size of fresh stool material are different according to the type of diet (p: <0.05), for particle size greater than 4.8 mm (sieve A), being the values for each diet: Pp: 47%, Ss: 27%, Mn: 13% and Aa: 2%. We also found relationships between parameters of nutritional quality of grazed forages and particle sizes in fresh feces with significant statistical levels (p <0.05), namely: DIG: A, r: -0.51 (p: 0) , 0037); DIG: D, r: 0.57 (p: 0.0008); FDN: A, r: 0.51 (p: 0.0034); FDN: D, r: -0.56 (p: 0.0011); FDA: A, r: 0.59 (p: 0.0005); FDA: A, r: 0.63 (p: 0.0001). Possibly, more evaluations about the forage / feces interaction with this method are needed to be able to define a descriptive model in this regard